Erythropoietic protoporphyria a clinical and molecular study from Lebanon: Ferrochelatase a potential tumor suppressor gene in colon cancer. Issue 5 (2nd August 2017) - Kadara, H.; Nemer, G.; Safi, R.; Rebeiz, N.; Daou, L.; Delbani, D.; Btadini, W.; Abbas, O.; Tofaili, M.; Bitar, F.; Kibbi, A.G.; Shimomura, Y.; et al.
Abstract : Erythropoietic protoporphyria (EPP) is a rare cutaneous and systemic disease caused by mutations in the ferrochelatase gene ( FECH ). The molecular underpinnings of EPP in Middle Eastern populations and relative to other ethnic groups secondary to increased consanguinity are unknown. To understand the molecular pathogenesis of Middle Eastern EPP, we surveyed clinicopathological and molecular features in 6 large consanguineous families from Lebanon and Syria presenting with cutaneous and systemic features consistent with EPP. We observed 30% increased liver disease and 20% elevated end‐stage liver complications in our EPP cohort compared to EPP patients previously reported elsewhere. In addition, Middle Eastern EPP patients in our cohort exhibited uniquely an increased incidence of colon cancer. Sequence analysis revealed 2 novel non‐synonymous FECH mutations in the studied families designated p.M294T and p.I230M. In addition, FECH activity was significantly decreased (6%) in fibroblasts obtained from sun‐exposed sites in a patient with p.M294T mutation, whereas in sharp contrast, protected sites from the same patient exhibited 54% activity for the gene. We also found that sun‐exposed fibroblasts, relative to sun‐protected and control fibroblasts, exhibited suppressed growth and atypical morphology in vitro, and that these effects were alleviated when the cells were co‐cultured with sun‐protected fibroblasts. Our findings on the increased incidence of colon cancer in EPP patients prompted us to survey FECH expression patterns in cancer. Using publicly available microarray datasets we found that FECH mRNA was largely significantly decreased in colon adenocarcinomas relative to normal colon tissues. Our findings suggest that families with autosomal recessive EPP should be screened more extensively for systemic involvement including liver diseases and colon cancer, and point to a previously unknown yet plausible tumor suppressor role for FECH in colon malignancy. Abstract :